Two new species of genus Apsilochorema Ulmer (Trichoptera: Hydrobiosidae) from India - Saini, Malkiat S.; K., Lakhwinder; Pandher, Manpreet S.; Parey, Sajad H. (Zootaxa, 2013)
Two new species of Apsilochorema (Trichoptera: Hydrobiosidae) from India are described, Apsilochorema (Archichore-ma) kashmirensis sp. nov. and Apsilochorema (Archichorema) meyi sp. nov., bringing to 12 the number of species in the genus known from the country.